2022
DOI: 10.1111/pcn.13495
|View full text |Cite
|
Sign up to set email alerts
|

The genome‐wide DNA methylation profiles among neurosurgery patients with and without post‐operative delirium

Abstract: Aims: There is no previous study demonstrating the differences of genome-wide DNA methylation (DNAm) profiles between patients with and without postoperative delirium (POD). We aimed to discover epigenetic (DNAm) markers that are associated with POD in blood obtained from patients before and after neurosurgery.Methods: Pre-and post-surgical blood DNA samples from 37 patients, including 10 POD cases, were analyzed using the Illumina EPIC array genome-wide platform. We examined DNAm differences in blood from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…[27] Furthermore, genome-wide DNA methylation profiles have been studied among neurosurgery patients with and without postoperative delirium, demonstrating heightened inflammatory cytokines such as IL-1β, IL-6, and TNF-α in the brain following surgical intervention. [28] These findings collectively emphasize the intricate relationship between inflammatory cytokines and the development of postoperative delirium, shedding light on the potential role of Dexmedetomidine in modulating the inflammatory response and its impact on POD. However, further research is warranted to elucidate the specific mechanisms through which Dexmedetomidine may influence the expression of inflammatory cytokines and subsequently affect the occurrence of postoperative delirium in surgical patients.…”
Section: Relevance To Existing Dexmedetomidine Researchmentioning
confidence: 69%
See 1 more Smart Citation
“…[27] Furthermore, genome-wide DNA methylation profiles have been studied among neurosurgery patients with and without postoperative delirium, demonstrating heightened inflammatory cytokines such as IL-1β, IL-6, and TNF-α in the brain following surgical intervention. [28] These findings collectively emphasize the intricate relationship between inflammatory cytokines and the development of postoperative delirium, shedding light on the potential role of Dexmedetomidine in modulating the inflammatory response and its impact on POD. However, further research is warranted to elucidate the specific mechanisms through which Dexmedetomidine may influence the expression of inflammatory cytokines and subsequently affect the occurrence of postoperative delirium in surgical patients.…”
Section: Relevance To Existing Dexmedetomidine Researchmentioning
confidence: 69%
“…[ 27 ] Furthermore, genome-wide DNA methylation profiles have been studied among neurosurgery patients with and without postoperative delirium, demonstrating heightened inflammatory cytokines such as IL‐1β, IL‐6, and TNF-α in the brain following surgical intervention. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory changes of microglia and macrophages in the immune system ( 43 ), inadequate blood flow and increased blood-brain barrier permeability in parenchymal vessels ( 44 ), decreased connectivity in nerve cell systems ( 45 ), and reduced mitochondrial efficiency ( 46 ) are among such mechanisms. In addition, our group has been focusing on the influence of age and investigating the potential role of epigenetic mechanisms, especially DNA methylation (DNAm), in the pathophysiological mechanism of delirium ( 47, 48 ). Our data clearly showed that DNAm in the TNF-alpha gene decreases along with age, together with the age associated increase of the gene expression.…”
Section: Discussionmentioning
confidence: 99%